2000
DOI: 10.1088/0031-9155/45/2/311
|View full text |Cite
|
Sign up to set email alerts
|

Photon beam characterization and modelling for Monte Carlo treatment planning

Abstract: Photon beams of 4, 6 and 15 MV from Varian Clinac 2100C and 2300C/D accelerators were simulated using the EGS4/BEAM code system. The accelerators were modelled as a combination of component modules (CMs) consisting of a target, primary collimator, exit window, flattening filter, monitor chamber, secondary collimator, ring collimator, photon jaws and protection window. A full phase space file was scored directly above the upper photon jaws and analysed using beam data processing software, BEAMDP, to derive the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
107
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(111 citation statements)
references
References 26 publications
4
107
0
Order By: Relevance
“…The linear accelerator beam information was included in a source model that was built and commissioned based on measured beam data. ( 25 26 ) The dose calculations were performed in a 3D rectilinear voxel geometry, which was created based on a CT scan of the ArcCHECK phantom. The material and density of each voxel was converted from the CT number based on a piecewise linear conversion curve.…”
Section: Methodsmentioning
confidence: 99%
“…The linear accelerator beam information was included in a source model that was built and commissioned based on measured beam data. ( 25 26 ) The dose calculations were performed in a 3D rectilinear voxel geometry, which was created based on a CT scan of the ArcCHECK phantom. The material and density of each voxel was converted from the CT number based on a piecewise linear conversion curve.…”
Section: Methodsmentioning
confidence: 99%
“…Our multiple SM consists of an extended annular source for the target, a planar ring source for the primary collimator, and a planar annular source for the flattening filter. ( 28 , 29 ) The geometry and spatial positions of each source in the SM follow the manufacturers’ specifications and are adjusted to yield the best match in the dose distributions between the original phase space and the reconstructed phase space from our multiple SM. The SMs were used in EGS4/MCSIM, and the dose in water was calculated and compared with ion chamber measurements in a water phantom.…”
Section: Methodsmentioning
confidence: 99%
“…Apart form using analytical source models or the PS file itself as a source model, another approach, which overcomes these limitations, is to create a histogram-based source model based on the PSD. 8,[12][13][14][15][16][17] By sampling the initial parameters of a particle from these histogram distributions, virtually no particle is reused, thereby reducing the latent variance. A further advantage of histogram-based source models is that the sampling is faster than reading particles from a PS file.…”
Section: Introductionmentioning
confidence: 99%
“…This benchmark allows investigating the shape of the dose distribution for each individual source, e.g., the change in depth for the dose maximum for each subsource, compared with other published studies in which the total dose distribution is shown. 11,12,[15][16][17]20 Furthermore, the subsource dose characterization has the potential to ease the commissioning procedure, since information about which subsource needs to be tuned can be obtained by comparing measured dose distributions with those calculated for the individual sources. Dose distribution comparisons are performed for SSDs of 50, 75, 100, and 200 cm to validate the source model for a large range of conditions.…”
Section: Introductionmentioning
confidence: 99%